2015
DOI: 10.3109/00365521.2015.1042031
|View full text |Cite
|
Sign up to set email alerts
|

Utility of baseline impedance level measurement in patients with gastroesophageal reflux symptoms

Abstract: BILs are related to GER, especially acid reflux. Location and duration of assessment for BILs needs to be standardized. Six-hour BILs could be substitutes for 24-h BILs. During analysis of MII-pH, more attention should be paid to BILs in the lower esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…[10,29] In our study, we found that there was a decreasing tendency in BILs from proximal esophagus to distal esophagus in RGERD patients and patients with acid reflux type. But the lowest distal BILs of RGERD patients were nearly 2 thousands of Ohms, which were higher than those from above-mentioned studies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[10,29] In our study, we found that there was a decreasing tendency in BILs from proximal esophagus to distal esophagus in RGERD patients and patients with acid reflux type. But the lowest distal BILs of RGERD patients were nearly 2 thousands of Ohms, which were higher than those from above-mentioned studies.…”
Section: Discussionmentioning
confidence: 66%
“…[911,29,30] Overall, it is reasonable to hypothesize that BILs decrease in parallel with the severity of GERD, from healthy to NERD, and then RE. Consistent with above studies, our data revealed that patients with severe esophagitis had lower distal BILs than those with mild esophagitis and NERD, and that patients with severe esophagitis in acid reflux type had lowest distal BILs.…”
Section: Discussionmentioning
confidence: 99%
“…Saritas Yuksel et al found that impedance values were similar at 10 cm above the LES for both GERD patients and healthy controls 28 . Consistently, the distal, but not the proximal BI values, were found to be lower in patients with reflux in a recent study 31 . These results could be interpreted as evidence that chronic exposure of the esophageal mucosa is less in the proximal esophagus in typical GERD patients.…”
Section: Discussionmentioning
confidence: 82%
“…28 Consistently, the distal, but not the proximal BI values, were found to be lower in patients with reflux in a recent study. 31 These results could be interpreted as evidence that chronic exposure of the esophageal mucosa is less in the proximal esophagus in typical GERD patients. In our study, we found that the proximal BI in patients with LPR symptoms was lower than in patients with typical symptoms without differences in their AET values.…”
Section: Discussionmentioning
confidence: 85%
“…In 2016, an IHC study collected the clinicopathological information of 28 patients received surgical resection for pancreatic cancer to determine the value of NLR as a prognostic factor in patients with pancreatic cancer. [ 23 ] Researchers found iNLR ≥ 5 was an important risk factor of poor disease-free survival and OS. Nevertheless, few studies focusing on iNLR in ESCC are available.…”
Section: Discussionmentioning
confidence: 99%